I Pursue Higher Education for Reasons: Exploring the Demand for Higher Education in Cambodia - Dom, Vannak (American Journal of Education and Learning, 2019)
This study was aimed at exploring higher education expectations of young students in Cambodia, one of the fastest economic growths in the region. In specific, the linkages of their expectation with social mobility, knowledge and gender stereotypes were explored. From the in-depth-interviews with 32 university students (12 men and 20 women), findings indicated that students have positive expectations in higher education in achieving broader knowledge, better job opportunity which could result in future upward social mobility and better standard of living. Having recognized the significance of higher education, students suggested that timely measures such as scholarship, housing, lower tuition fee etc. should be taken to assist the poor, especially for women. This paper concludes that social mobility is a strong motivation among the children. However, the social mobility should be fairly facilitated and strong encouraged by family, state, community and individuals themselves.